Meningkatkan Loyalitas Pelanggan Melalui Pelayanan Prima - Telaumbanua, Rani Farnida; Rahayu, Enik (Mahesa Research Center, 2025)
This article aims to analyze service factors that influence customer loyalty in Kampoeng Djawa and strategies implemented by management to improve customer satisfaction. The problem focuses on the relationship between excellent service and customer loyalty, including obstacles faced and efforts to improve them. In order to approach this problem, this study uses theoretical references from the concepts of customer satisfaction, customer loyalty, and excellent service strategies. Data were collected through interviews with customers and employees and direct observation of the service system in Kampoeng Djawa. Analysis was conducted qualitatively to understand the pattern and impact of service on customer loyalty. The results showed that staff friendliness, speed of service, and product availability were the main factors in building customer loyalty. The strategies implemented, such as employee training, efficient queuing systems, and customer complaint services, contributed to improving customer satisfaction. The main obstacles faced included a surge in customers during peak hours, limited product stock, and variation in employee skills, which were addressed through additional staff, better stock monitoring, and regular training. This study concludes that consistent and innovative excellent service can improve customer loyalty and strengthen Kampoeng Djawa's competitiveness in the retail industry